FUNGSI HUKUM ADAT DALAM PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Saiful Anam (Yayasan Merassa Indonesia Publikasi, 2023)
In the formation of laws and regulations, we tend to forget customary laws that have existed and are used in everyday life. The formation of laws and regulations based on cultural values and the nation's cultural culture needs serious attention. The search for customary law that applies in Indonesia to then be used as a basis for the formation of national law is very crucial in the midst of the decline in the adoption of the nation's cultural values so that customary law can be used as a reflection in the formation of law both at the central and regional levels in Indonesia. This writing uses sociological normative writing methods that will provide an elaboration of the position and position of the Customary Constitution in the Indonesian legal system. Through the writing of this journal, it is expected to provide an understanding of how important the position of the Customary Constitution is in legal development in the modern era. With the actualization of Customary Law in the formation of Law, it is hoped that we can nurture the wealth of noble values of the nation and be maintained as part of the nation's wealth, and Customary Law will still be used as a reference in every life of the nation and state in Indonesia. Abstrak Dalam pembentukan peraturan perundang-undangan, kita cenderung melupakan hukum adat yang selama ini pernah ada dan digunakan dalam keseharian. Pembentukan hukum dan peraturan perundang-undangan yang berbasis pada nilai-nilai budaya dan kultur budaya bangsa perlu mendapatkan perhatian serius. Penelusuran hukum adat yang berlaku di Indonesia untuk kemudian dijadikan dasar dalam pembentukan hukum nasional menjadi hal yang sangat krusial di tengah merosotnya pengangkatan tata nilai kebudayaan bangsa sehingga hukum adat dapat dijadikan cerminan dalam pembentukan hukum baik di tingkatan pusat dan daerah yang ada di Indonesia. Penulisan ini menggunakan metode penulisan normatif sosiologis yang akan memberikan penjabaran tentang posisi dan kedudukan Konstitusi Adat dalam sistem hukum Indonesia. Melalui penulisan jurnal ini diharapkan memberikan pemahaman betapa pentingnya posisi Konstitusi Adat dalam pembangunan hukum di era modern. Dengan adanya pengaktualisasian Hukum Adat dalam pembentukan Hukum, maka diharapkan kekayaan nilai-nilai luhur bangsa dapat kita pupuk dan dipertahankan sebagai bagian dari kekayaan bangsa, serta Hukum Adat akan tetap dijadikan rujukan dalam setiap kehidupan berbangsa dan bernegara di Indonesia.